The Influence of Authority Parenting Patterns on Children's Interest in Learning Islam - Zaldi, Ahmad; Abdullah, Mulyana; Kristina, Kristina; Dewi, Dian Fitriani; Novianti, Resa (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Parenting patterns are behavioral patterns of parental activities in caring for, nurturing, and guiding their children to be independent, grow, and develop healthily. This study aims to determine the extent of the influence of authoritarian parenting patterns on students of the Integrated Islamic Senior High School (SMAIT). The population in this study was all SMAIT Imam Malik Bandung and the sample selected was class X (ten) consisting of 8 female students. Data collection using literature study and questionnaire methods. This study began with data collection, data analysis, and conclusions. The type of data used is quantitative data. Data collection using the Likert Scale. Data analysis techniques using the SPSS program. Version.20. The study results showed an influence of authoritarian parenting patterns on learning interest in Islamic Religion learning at SMAIT Imam Malik Bandung based on r results or person correlation of 0.364, indicating the perfect correlation interval. R count (0.364)> R table (0.220). With these results, there is an influence of authoritarian parenting patterns on children's learning interest in the Islamic Religion. The results of the calculation of the coefficient of determination or R Square of authoritarian parenting patterns contribute to an increase in learning interest by 2.2% this shows the magnitude of the increased learning interest at SMAIT Imam Malik Bandung. The significant value of 0.000, compared to the significance level of 0.05 (5%), is smaller than 0.05 (%). Based on the calculation results, the null hypothesis (Ho) is rejected, and the working hypothesis (Ha) is accepted, this means that there is an influence of parenting patterns.